2011
DOI: 10.1007/s13197-011-0547-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of gluten free cookies prepared from different flour combinations

Abstract: The present investigation was undertaken on the utilization of alternate flours/meals (rice (Oryza sativa), maize (Zea mays), sorghum (Sorghum vulgare) and pearl millet (Pennisetum glaucum) for the preparation of gluten free cookies as compared to conventional wheat (Triticum aestivum) flour cookies. The physicochemical parameters, sensory qualities and functional properties of flours/cookies were studied and compared with control cookies. The blend of maize and pearl millet had best pasting qualities followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 9 publications
5
55
0
2
Order By: Relevance
“…Each observation is a mean of 6 replicate experiments. For each observation the coefficient of variation was less than 0.5 % protein complex found in wheat which provides desirable organoleptic properties (texture and taste) to many bakery and other food products (Rai et al 2011). However gluten seems to play a limited role in defining the processability and end product quality of cookies.…”
Section: Functional Properties Of Precooked Taro Flourmentioning
confidence: 97%
See 1 more Smart Citation
“…Each observation is a mean of 6 replicate experiments. For each observation the coefficient of variation was less than 0.5 % protein complex found in wheat which provides desirable organoleptic properties (texture and taste) to many bakery and other food products (Rai et al 2011). However gluten seems to play a limited role in defining the processability and end product quality of cookies.…”
Section: Functional Properties Of Precooked Taro Flourmentioning
confidence: 97%
“…In this respect it has been suggested that soft wheat flour or composite flour is preferred for production of good quality biscuits (Eneche 1999). Practically the sensory acceptability of the biscuits is the most used parameter to assess the limit of substitution and many studies reported with success acceptable biscuits at very high levels of substitution with non-wheat flours (Rai et al 2011;Eneche 1999) (Table 4). Composition and sensory characteristics of biscuits composite…”
Section: Functional Properties Of Precooked Taro Flourmentioning
confidence: 99%
“…This is due to longer shelf life, prepared in local bakeries also, easy marketing, low cost, varied taste and texture. The use of millet flour is becoming more and more common in baked products especially in bread, cookies and crackers that are targeted at consumers who are gluten sensitive or diabetic (Lovis, 2003;Rai et al 2014;Tanwar and Dhillon, 2017). The bakery products such as cookies are predominantly based on refined wheat flour and the replacement of refined wheat flour with finger millet will upgrade the nutritional quality of such products.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently there is an increasing demand for gluten-free food products which has augmented the research efforts as well (Rai et al 2014;Shevkani and Singh 2014). Ingestion of gluten containing foods by celiac patients causes atrophy of the small intestinal villi and ultimately leads to several symptoms such as cramping, bloating, nausea, diarrhoea, anaemia, fatigue, weight loss and vitamin and mineral deficiencies (Green and Cellier 2007).…”
Section: Introductionmentioning
confidence: 99%